Faith-Filled Visions for a Vital Earth Community: Deep Sustainability, Theo-Ecoethics, and Laudato Si’ - Hrynkow, Christopher (Religious studies and theology, 2018)
The world is faced with virulent social and ecological crises. Associated challenges like global climate change, poverty, racism, biodiversity loss, sexism, and ecological degradation cry out for deeply sustainable solutions. Such solutions can help achieve a situation of socio-ecological flourishing. Synthesizing these premises, this article employs a theo-ecoethical perspective to map Pope Francis’s vision for sustainable social and ecological relationships as sourced in his first social encyclical, Laudato Si’. Through this approach it is demonstrated that in contrast to the premise that Christian belief in the afterlife mitigates against caring for the natural world, the Pope has articulated a faith-filled vision that supports socio-ecological flourishing.